2018
DOI: 10.1002/glia.23551
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic dependence of glioma cells on kish/TMEM167A regulation of vesicular trafficking

Abstract: Genetic lesions in glioblastoma (GB) include constitutive activation of PI3K and EGFR pathways to drive cellular proliferation and tumor malignancy. An RNAi genetic screen, performed in Drosophila melanogaster to discover new modulators of GB development, identified a member of the secretory pathway: kish/TMEM167A. Downregulation of kish/TMEM167A impaired fly and human glioma formation and growth, with no effect on normal glia. Glioma cells increased the number of recycling endosomes, and reduced the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 42 publications
4
38
0
Order By: Relevance
“…We observed an increase in the survival of the mice that had been injected with shTMEM167A cells in comparison with the control-injected mice ( Figure 5A). Moreover, TMEM167A knock-down (KD) induced a decrease in the amount of Phospho-AKT ( Figure 5B), confirming our previous results [10] and demonstrating an efficient inhibition of EGFR signaling after the in vivo downregulation of TMEM167A. Even though this established cell line overexpresses EGFR, U87 cells do not carry alterations in this gene.…”
Section: Tmem167a Controls the Orthotopic Growth Of Wild-type P53 Glisupporting
confidence: 89%
See 2 more Smart Citations
“…We observed an increase in the survival of the mice that had been injected with shTMEM167A cells in comparison with the control-injected mice ( Figure 5A). Moreover, TMEM167A knock-down (KD) induced a decrease in the amount of Phospho-AKT ( Figure 5B), confirming our previous results [10] and demonstrating an efficient inhibition of EGFR signaling after the in vivo downregulation of TMEM167A. Even though this established cell line overexpresses EGFR, U87 cells do not carry alterations in this gene.…”
Section: Tmem167a Controls the Orthotopic Growth Of Wild-type P53 Glisupporting
confidence: 89%
“…Recently, we have shown that the downregulation of TMEM167A or its fly orthologue, Kish, diminish glioma growth by affecting the endo-lysosomal system. Moreover, our previous data suggested that the downregulation of TMEM167A/Kish induces degradation of EGFR [10]. However, we had not explored the relation between TMEM167A expression and/or function with the genetic status of EGFR and TP53.…”
Section: Analysis Of Vesicular Transport-related Genes Associated Witmentioning
confidence: 96%
See 1 more Smart Citation
“…Glial cells respond to this oncogenic transformation and reproduce all main features of the disease, including glial expansion and invasion, but in a shorter period of time. This Drosophila model has been used for drug and genetic screenings and the results have been validated in human GB cells (REFs) (12)(13)(14).Agents involved in the battlefield GB growth and migration are driven by specific signaling pathways as well as interactions between the tumor and its extracellular microenvironment. In our study, we include the cell membrane protrusions (TMs) as driving factors of tumor progression, as well as cell response to signaling gradients and the interplay with the Extra Cellular Matrix (ECM).…”
mentioning
confidence: 99%
“…Glial cells respond to this oncogenic transformation and reproduce all main features of the disease, including glial expansion and invasion, but in a shorter period of time. This Drosophila model has been used for drug and genetic screenings and the results have been validated in human GB cells (REFs) (12)(13)(14).…”
mentioning
confidence: 99%